(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
جاء الإيمان حالة جديدة خالفت الواقع الدِّينيَّ السَّائد في المرحلة الَّتي سبقت الإسلام، فاخترقت جدار هذا المجتمع، وأسَّست لمرحلة جديدة، غيَّرت وجه التَّاريخ، كما شطرت المجتمع العربي إلى فئتين: فئة المؤمنين المجاهدين في سبيل الله، وفئة الكفَّار والعصاة، الَّذين حاربوا الدَّعوة وحامل لوائها الرَّسول الأعظم(ص)،الَّذي حمل راية الجهاد بكلِّ أنواعه ،فلم يقتصر على نوع أو معنى واحد، إنَّما أخذ معاني متعدِّدة، وظهر بأشكال مختلفة، فتميَّز بثبات المؤمن وقوَّة عقيدته، ورسوخ إيمانه في وجه الظُّلم والطُّغيان، وقد أخذ الشِّعر على عاتقه رصد كلِّ مايدور حوله من أحداث ـ قولاً وفعلاً ـ صدرت عن أشخاص كانوا محورها، وقد قام الشُّعراء بترجمتها شعراً ،ورسم الصُّور الإيمانية الجديدة لكوكبة من المؤمنين الأشدَّاء وعلى رأسهم الرَّسول الأعظم(ص)، وقد استطاعت هذه الصُّور قراءة الأبعاد الحقيقية لمعاني الإيمان ، كما منح الشِّعر هذه الصور أبعادها الإيمانية الحقيقية، وجعلها أنموذجاً يحتذى، لبناء واقع جديد. belief came as a new state, contradicted the actual dominant religion in pre-Islamic era, which, so that it penetrated the wall of that society, and laid the foundation for a new period, which changed the face of history, and divided the Arabian society into two groups: the group of faithful combatants, and the group of unfaithful and disobeying one, who combated the Islamic mission and its flag carrier, who, raised high the flag of all types of Jihad, which had a several means, and appeared in various forms, and it was also recognized by the steadiness of the faithful and the power of their credibility. So poetry had the mission of observing all the events going on around (deeds and words) done and said by the people who were the axis of the events, and which poets translated into poetry, and drew the new faithful image of a group of powerful believers whom the greatest prophet comes ahead of them. The images were able to read the real dimension of the meanings of faithfulness. Poetry also gave these images their real faith dimension and made them as a model that must be followed to achieve a new reality.